EVALUATION OF PROPHYLACTIC ANTIBIOTIC USE IN SURGICAL PATIENTS USING THE GYSSENS METHOD AT A PRIVATE HOSPITAL IN YOGYAKARTA - Arviani, Septania Dini; Faridah, Imaniar Noor; Amsriza, Fadli Robbi (Jurnal Farmasi Sains dan Praktis, 2025)
Prophylactic antibiotics are used before, during, and up to 24 hours after surgery, and can be administered to patients 30-60 minutes before surgery, must adhere to the principle of “Right Antibiotics”. This study aims to assess the application of prophylactic antibiotics in surgical patients in a private hospital in Yogyakarta to promote rational antibiotic use. This study is quantitative and non-experimental. Data were collected prospectively over a period of 30 days from August 4 to September 4, 2024. The study sample consisted of all surgical patients who received prophylactic antibiotics. Prophylactic antibiotic data were analyzed using the Gyssens method. Out of the data collected, 110 patients received preventive antibiotics, and 97 of these patients met the inclusion criteria. Patient characteristics predominantly included a 46% incidence of cesarean sections. Prophylaxis employed three antibiotics, viz. ceftriaxone in 78 patients (79.38%), cefazolin in 19 patients (19.59%), and cefotaxime in 1 patient (1.03%). The assessment utilizing the Gyssens approach revealed that 31 patients were classified into category V (no indication), 49 patients into category IVA (more effective antibiotics available), and one patient into category I (not suitable during prophylaxis). Sixteen patients in category 0 were included in the reasonable antibiotic regimen. This study states that most antibiotics are not in accordance with the Guidelines for Antibiotic Use established by the Ministry of Health of the Republic of Indonesia in 2021.